Training requirements of agricultural extension officers using Borich needs assessment model - Saleh, Jasim Mohammed; Man, Norsida (Routledge, 2017)
This study is based on the opinions of selected Iraqi extension workers, regarding the type and amount of training they need, given their experience in the field. The Borich Needs Assessment Model was used for measuring training needs. The data were collected through questionnaires given to 300 respondents (agricultural workers) from January 15, 2016 to March 20, 2016. The results show that crop-planting courses have the greatest benefit. The greatest training need is skill and knowledge of teaching methods, while a moderately needed skill is the use of computer and information and communication technologies (ICT); management skills are the least needed training.